Charge compensation mechanisms of BaTiO3 ceramics co-doped with La2O3 and Bi2O3. Issue 4 (15th February 2022) - Ma, Cuiying; Du, Huiling; Liu, Jia; Du, Xian; Feng, Danni
Abstract: Doping modification is commonly used to improve the electrical properties of BaTiO3 (BT). In this study, the ((1- x )BT- x (Bi2 O3 –La2 O3 )) ceramics were synthesised to investigate the charge balance compensation mechanisms of BT ceramics co-doped with La2 O3 and Bi2 O3 as donors at A-site. The XRD results showed that a pseudo-cubic phase was formed by intruding dopants. The Raman spectroscopy revealed that the samples, which x  = 0.10 and 0.16, had relatively more oxygen and titanium vacancies. After heat-treatment the samples in oxygen atmosphere, the dielectric constant of the sample with x  = 0.10 was higher than that of the untreated, but for x  = 0.16, it was almost no changed. These results indicated that the different charge balance compensation mechanism was exist in the samples with x  = 0.10 and 0.16. Impedance measurements showed that the resistance tendency exhibited initial decrease and subsequent increase, leading to the electronic and ionic compensation mechanisms with x  = 0.10 and 0.16, respectively. Ferroelectric properties also implied charge balance compensation mechanism transition, due to P s and P r were higher for x  = 0.10 than for x  = 0.16, respectively. This work provides a new strategy for modulating the electric properties of BT-based ceramics.